2015
DOI: 10.1021/acs.jafc.5b04674
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Accumulation, Antioxidant Ability and Stability, and a Transcriptional Analysis of Anthocyanin Biosynthesis in Purple Heading Chinese Cabbage (Brassica rapa L. ssp. pekinensis)

Abstract: Heading Chinese cabbage (Brassica rapa L. ssp. pekinensis) is a significant dietary vegetable for its edible heading leaves in Asia countries. The new purple anthocyanin-rich pure line (11S91) was successfully bred, and the anthocyanins were mainly distributed in 2-3 cell layers beneath the leaf epidermis, whereas siliques and stems accumulated only a cell layer of anthocyanins. The anthocyanins of 11S91 were more stable at pHs below 3.0 and temperatures below 45 °C. The total antioxidant ability was highly po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 50 publications
4
61
2
Order By: Relevance
“…The same is true for B. rapa , B. oleracea and B. napus , whose genomes do not contain CYP75A sequences (Chen et al ., unpublished data). However, delphinidin‐based anthocyanins were previously found in B. rapa (purple bok choy) (Zhang et al ., ) and purple heading Chinese cabbage (He et al ., ) as well as in the present study in B. napus , in which three types of known delphinidin and one type of new delphinidin were identified in red petals and one type of delphinidin was identified in yellow petals. Thus, it was interesting to investigate whether B. rapa and B. napus contain isoenzymes that share the same catalytic activity as F3′5′H.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The same is true for B. rapa , B. oleracea and B. napus , whose genomes do not contain CYP75A sequences (Chen et al ., unpublished data). However, delphinidin‐based anthocyanins were previously found in B. rapa (purple bok choy) (Zhang et al ., ) and purple heading Chinese cabbage (He et al ., ) as well as in the present study in B. napus , in which three types of known delphinidin and one type of new delphinidin were identified in red petals and one type of delphinidin was identified in yellow petals. Thus, it was interesting to investigate whether B. rapa and B. napus contain isoenzymes that share the same catalytic activity as F3′5′H.…”
Section: Discussionsupporting
confidence: 85%
“…The most preferentially accumulated anthocyanin in red petals showed peaks at retention times of 9.9 and 10.4 and a molecular weight of 1005.2124 ( Figure S7a). MS data ([M]+, m/z 1005; MS/MS, m/z 757/535/287) indicated that it was a known anthocyanin, cyanidin 3-coumaroyldiglucoside-5-malonylglucoside ( Figure S7b) (He et al, 2016;Sun et al, 2013;Zhang et al, 2014b). One new anthocyanin with a molecular weight of 713.1562 was found to be delphinidin-3-malonyl glucoside-5-glucoside, according to the MS data ([M]+, m/z 713; MS/MS, m/z 551/465/303), but this identification requires further confirmation by other methods.…”
Section: Camv35s-driven Overexpression Of Ovpap2 In a Thaliana And Bmentioning
confidence: 99%
“…Total anthocyanin extraction and determination were measured using an UV-visible spectroscopy method as previously with a few modifications [39]. Crushed samples (1.0 g) were extracted using the 1% hydrochloric acid water solution (10 mL), and measured at λ max 530 nm and 700 nm using a UV-visible spectrophotometer (Thermo Fisher Scientific, Wilmington, USA) in a 0.2-M potassium chloride buffer (pH 1.0) and a 0.45-M sodium acetate buffer (pH 4.5), respectively.…”
Section: Total Anthocyanins Analysismentioning
confidence: 99%
“…Total RNA extraction, cDNA synthesis, and the qRT-PCR reactions in IQ5 optical system (Bio-Rad, USA) were performed as described previously [39]. The synthetic cDNA was diluted to 50 ng µL −1 with double-distilled water using a microspectrophotometer (Thermo Fisher Scientific, Wilmington, DE, USA).…”
Section: Identification Of Anthocyanin Biosyntheis Genes and Quantitamentioning
confidence: 99%
“…In Brassica vegetables, fifteen to twenty-four anthocyanins from the leaves of red cabbage were detected by HPLC [ 13 , 14 , 15 ]. Twenty to thirty kinds of anthocyanins have been identified in purple Chinese cabbage [ 16 , 17 , 18 ]. In the deep purple pakchoi line, eight to twenty species of anthocyanins have been investigated [ 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%